Rancang Bangun Sistem Keamanan Kunci Kontak Sepeda Motor Berbasis Android - Ramli, Ramli; Budi, Budi (Jurnal Ilmu Komputer dan Sistem Komputer Terapan (JIKSTRA), 2022)
In this study, a motorcycle ignition lock security system was designed and implemented using Arduino and Android so that the owner felt safe against the motorcycle left in the parking lot. This Android application system has 2 functions, namely: activating and turning off the alarm on the motorcycle. This system will be controlled via android, which has good bluetooth quality. To connect between the android phone and the system installed on the vehicle, bluetooth will be used, where the data sent will be received by the bluetooth module and will be processed in the microcontroller installed on the vehicle so that the microcontroller will command the system to work. The design and implementation of this system can already be connected to the existing hardware on the motorcycle by turning on and off the alarm. The maximum distance between the android and the motorbike is 10 meters, if more than that the bluetooth on the motorbike is not detected. The purpose of designing a tool that can lock a motorcycle with an android device is to provide a sense of security to the motorcycle owner when leaving his motorcycle in the parking lot. The research methods carried out include, literature study, observation, interviews, collecting information and data, analysis, design, system implementation and system testing. As a conclusion from the results of this system design is the production of a motorcycle ignition lock security system so that it can provide a sense of security for the owner.